Subclinical gut inflammation in spondyloarthropathy patients is associated with upregulation of the E-cadherin/catenin complex. Issue 3 (1st March 2000) - Demetter, P; Baeten, D; De Keyser, F; De Vos, M; Van Damme, N; Verbruggen, G; Vermeulen, S; Mareel, M; Elewaut, D; Mielants, H; Veys, E M; Cuvelier, C A
Abstract : OBJECTIVE: Previously an upregulation of E-cadherin and its associated molecules α-catenin, β-catenin and plakoglobin has been demonstrated in clinically overt inflammatory bowel disease (IBD). The aim of this study was to investigate the expression of the E-cadherin/catenin complex in subclinically inflamed bowel mucosa from spondyloarthropathy (SpA) patients. METHODS: Ileal and colonic biopsy specimens from 19 SpA patients with subclinical inflammatory gut lesions and from seven controls were stained with monoclonal antibodies against E-cadherin, β-catenin and plakoglobin and a polyclonal antibody against α-catenin. E-cadherin mRNA was detected using a riboprobe. Inflammation was histologically classified into acute, chronic active and chronic quiescent forms. RESULTS: In acute and chronic active bowel inflammation of SpA patients, upregulation of the E-cadherin/catenin glycoprotein complex could be observed. Chronic lesions in a quiescent state did not show such an upregulation. Furthermore, chronic inflammation was associated with an increase in E-cadherin mRNA. CONCLUSIONS: As some of the SpA patients with subclinical gut inflammation develop IBD, upregulation of the E-cadherin/catenin complex in inflamed bowel mucosa from SpA patients may point to early cellular changes in the development of IBD. However, at present it cannot be excluded that increased E-cadherin/catenin complex expression is a bystander phenomenon of active inflammation.